Deep Learning for Protein Structure Prediction: A New Era in Drug Design - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Keywords: Deep Learning, Protein Structure Prediction, Drug Design, AlphaFold, Artificial Intelligence, Computational Biochemistry, Drug Discovery
Keywords: Drug Discovery; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning